Effectiveness of zinc-fortified water on zinc intake, status and morbidity in Kenyan pre-school children: a randomised controlled trial. Issue 15 (7th June 2018) - Kujinga, Prosper; Galetti, Valeria; Onyango, Elizabeth; Jakab, Viktor; Buerkli, Simone; Andang'o, Pauline; Brouwer, Inge D; Zimmermann, Michael B; Moretti, Diego
Abstract: Objective: Zn deficiency and diarrhoea are prevalent and may coexist in children living in low-resource settings. Recently, a novel approach for delivering Zn via microbiologically treated, Zn-fortified water was shown to be effective in improving Zn status in West African schoolchildren. We assessed the effectiveness of Zn-fortified, microbiologically purified water delivered as a household intervention on Zn intake, status and morbidity in children aged 2–6 years from rural western Kenya. Design: Randomised controlled trial. Intervention included households assigned to water treatment device with (ZFW) or without (FW) Zn delivery capability Setting: Rural households in Kisumu, western Kenya. Subjects: Children aged 2–6 years. Results: The ZFW group had higher dietary Zn intake compared with the FW group. ZFW contributed 36 and 31 % of daily requirements for absorbable Zn in children aged 2–3 and 4–6 years, respectively, in the ZFW group. Consumption of Zn-fortified water resulted in lower prevalence of reported illness (risk ratio; 95 % CI) in the ZFW group compared with the FW group: for cold with runny nose (0·91; 0·83, 0·99; P =0·034) and abdominal pain (0·70; 0·56, 0·89; P =0·003) in the intention-to-treat analysis and for diarrhoea (0·72; 0·53, 0·96; P =0·025) in the per-protocol analysis. We did not detect an effect of treatment on plasma Zn concentration. Conclusions: Daily consumption of Zn-fortified, microbiologically treated water results in increased intake of absorbable dietary Zn and may help in preventing childhood infections in pre-school children in rural Africa.